Optically tailored magnetic potentials for ultracold atoms based on superconducting vortices - Phyo, Baw Swe (2019)
Atom chips are micro-fabricated devices which create versatile magnetic poten- tials for trapping, cooling and controlling ensembles of ultra-cold atoms. Ad- vancing from the typical atom chips, currents from superconducting vortices are used to trap and manipulate the ultra-cold atoms in our experiments. The su- perconducting vortex traps can be configured by controlling strength and pulse time of external magnetic fields together with bias fields. In order to fully utilize reconfigurability, superconducting vortices are optically manipulated with laser light to generate desired vortex patterns with this tailored trapping potentials for ultra-cold atoms are created. We have carried out heat diffusion simulations of laser patterns and characterized laser power and pulse time to effectively config- ure the desired vortex potentials. We have also successfully manipulated vortex matter optically to create arbitrary vortex patterns and ring potentials for cold atoms to utilize in quantum simulations and on-chip matter wave interferom- etry applications. Moreover, cold atoms could be used as a sensitive probe to examine magnetic field distribution of the superconducting vortices and we have used this technique to experimentally verify the resulting magnetic potentials of superconducting vortices after optical manipulation.